An integrated plastic microchip for enhancing electrophoretic separation using tunable pressure‐driven backflows. Issue 7 (19th January 2022) - Liu, Yulan; Xia, Ling; Xiao, Xiaohua; Li, Gongke
Abstract: Microfluidic CE (MCE) is an effective solution for rapid and sensitive determination of multiple analytes. Herein, a dynamic coated cyclic olefin copolymer microchip was developed having an on‐chip micropump for fluid velocity adjusting in electrophoretic separations. This micropump was fabricated by constructing a polyacrylamide gel membrane at one channel terminal. Once applying electric field across the membrane, a pressure‐driven flow generated automatically to balance the electroosmotic flow (EOF) mismatch at the channel‐membrane interface. The influence of gel precursor concentration and operating voltages on the fluid velocity was carefully evaluated. Moreover, the highly integration of injection, separation, and pumping units of the MCE system minimized the dead volume and provides satisfied column efficiency. Experiments showed that by adjusting of pumping voltage reduced the fluid velocity by a factor of 6, resulting six‐ and threefold resolving power enhancements of rhodamine dye mixture and amino acid mixture, respectively. Furthermore, the developed MCE method was applied for rhodamines and amino acids quantitation in food and cosmetics, with standard addition recoveries of 87.3–106.9% and 89.9–117.4%, respectively. These results were also confirmed by standard HPLC method, revealing the application potential in fast and onsite analysis of complex samples.